Synthesis of TiO2 Nanoparticles and Their Catalytic Activity - Zhou, Wei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue of "Synthesis of TiO2 Nanoparticles and Their Catalytic Activity" contains 10 research and review articles, which present the recent advances in the synthesis and applications of TiO2 nanomaterials for photocatalytic water splitting, environmental remediation, antibacterial, and bioimplant. In this issue, photocatalysts such as Ti2O3, TiN, g-C3N4, and reduced graphene oxide could be combined with TiO2 to form heterojunctions, thus enhancing photocatalytic performance. Besides anatase TiO2, rutile TiO2 with oxygen vacancies also demonstrated marvelous photoluminescence emission properties. In addition, the cutting-edge progress in black TiO2 nanomaterials are summarized in this issue. The advances of TiO2 catalysis and generation mechanism of reactive oxygen species w/o light irradiation were also concluded to analyze the safety and complexity of Ti-oxides in disinfection and bioimplants.